2020
DOI: 10.21203/rs.3.rs-41739/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term Experience with Triheptanoin in 12 Austrian Patients with Long-chain Fatty Acid Oxidation Disorders

Abstract: BackgroundLong-chain fatty acid oxidation disorders (LC-FAOD) are a group of rare inborn errors of metabolism with autosomal recessive inheritance that may cause life-threatening events. Treatment with triheptanoin, a synthetic seven-carbon fatty acid triglyceride compound with an anaplerotic effect, seems beneficial, but clinical experience is limited. We report our long-term experience in an Austrian cohort of LC-FAOD patients.MethodsWe retrospectively assessed clinical outcome and total hospitalization days… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…6,7 Furthermore, triheptanoin has been studied clinically over 13 years, and the available literature provides clinical responses associated with LC-FAODs. [8][9][10][11][12][13] Triheptanoin is extensively hydrolyzed into glycerol and heptanoate (C7 fatty acids) in the gastrointestinal (GI) tract by pancreatic lipases, and subsequently, heptanoate is absorbed through the gut wall. 14 Heptanoate can diffuse across the mitochondrial membranes and undergo a series of beta-oxidative metabolic reactions to generate acetyl coenzyme A (CoA) and propionyl-CoA, bypassing the carnitine shuttle and long-chain fatty acid oxidation enzymes that are deficient in patients with LC-FAODs.…”
mentioning
confidence: 99%
“…6,7 Furthermore, triheptanoin has been studied clinically over 13 years, and the available literature provides clinical responses associated with LC-FAODs. [8][9][10][11][12][13] Triheptanoin is extensively hydrolyzed into glycerol and heptanoate (C7 fatty acids) in the gastrointestinal (GI) tract by pancreatic lipases, and subsequently, heptanoate is absorbed through the gut wall. 14 Heptanoate can diffuse across the mitochondrial membranes and undergo a series of beta-oxidative metabolic reactions to generate acetyl coenzyme A (CoA) and propionyl-CoA, bypassing the carnitine shuttle and long-chain fatty acid oxidation enzymes that are deficient in patients with LC-FAODs.…”
mentioning
confidence: 99%
“…Recent studies suggest a beneficial effect of treatment with beta-hydroxybutyrate and triheptanoin in patients with (long-chain) fatty acid oxidation disorders. [30][31][32][33] The reported LCKATD patient, who was treated with sodium-D,L-3-hydroxybutyrate, had a longer survival time than LCKATD patients previously reported in the literature and potentially benefited from this treatment. However, both treatment strategies require tolerance for enteral feeding, which is a sometimes unavoidable obstacle in the treatment of critically ill patients.…”
Section: Discussionmentioning
confidence: 75%
“…This implies that the currently available treatment options are insufficient and improved treatment strategies are needed. Recent studies suggest a beneficial effect of treatment with beta‐hydroxybutyrate and triheptanoin in patients with (long‐chain) fatty acid oxidation disorders 30–33 . The reported LCKATD patient, who was treated with sodium‐D,L‐3‐hydroxybutyrate, had a longer survival time than LCKATD patients previously reported in the literature and potentially benefited from this treatment.…”
Section: Discussionmentioning
confidence: 84%
“…A retrospective observational study in an Austrian cohort of 8 paediatric patients with LC-FAOD treated with triheptanoin found that total hospitalization days/year decreased from a mean 27.1 days /year in the year prior to initiating triheptanoin treatment to a mean 8.2 days/year in the year after starting treatment [14].…”
Section: What Is the Efficacy Of Triheptanoin In Lc-faods?mentioning
confidence: 99%